The credibility of monetary policy announcements: Empirical evidence for OECD countries since the 1960s - Ansgar Belke; Andreas Freytag; Jonas Keil; Friedrich Schneider (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Monetary policy rules have been considered as fundamental protection against inflation. However, empirical evidence for a correlation between rules and inflation is relatively weak. In this paper, we first discuss likely causes for this weak link and present the argument that monetary commitment is not credible in itself. It can grant price stability best if it is backed by an adequate assignment of economic policy. An empirical assessment based on panel data covering five decades and 22 OECD countries confirms the crucial role of a credibly backed monetary commitment to price stability.
Keywords: E31; E50; E52; 330; credibility; central bank independence; price stability; monetary commitment